2020
DOI: 10.18502/npt.v7i4.4034
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of exclusive breastfeeding: An integrative review

Abstract: Background & Aim: The importance of breastfeeding and its exclusivity in the first six months of a child’s life is worldwide recognized. Despite that adherence to exclusive breastfeeding is far from international standards. Therefore, updating evidence on this topic is essential to demonstrate to parents and health professionals the benefits of exclusive breastfeeding, demystifying ideas, and promoting adherence. Methods & Materials: An integrative review was conducted with a search in Medline, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 0 publications
3
18
0
2
Order By: Relevance
“…For babies, EBF was identified such as healthier eating habits, reduced length of hospital stay, favorable weight increase, lower body mass index, lower adiposity, lower total cholesterol values, better cognitive and behavioral development, as well as stability of metabolic levels in children with metabolic disorders. Meanwhile, for mothers, EBF can protect mothers from the risk of ovarian and breast cancer because it is a portion of safe baby food and also reduces obesity (MacVicar, Humphrey and Forbes-McKay, 2018;Fan et al, 2019;Couto, Dias and Oliveira, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For babies, EBF was identified such as healthier eating habits, reduced length of hospital stay, favorable weight increase, lower body mass index, lower adiposity, lower total cholesterol values, better cognitive and behavioral development, as well as stability of metabolic levels in children with metabolic disorders. Meanwhile, for mothers, EBF can protect mothers from the risk of ovarian and breast cancer because it is a portion of safe baby food and also reduces obesity (MacVicar, Humphrey and Forbes-McKay, 2018;Fan et al, 2019;Couto, Dias and Oliveira, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analyses of three studies (Flax et al, 2014;Jiang et al, 2014;Sellen et al, 2013) judged to be sufficiently homogenous showed that delivering prenatal breastfeeding interventions using SMS/cell phone (vs routine prenatal care) improved rates of initiation of breastfeeding within one hour after birth and increased the likelihood of exclusive breastfeeding for up to six months, although there was no strong evidence regarding the giving of colostrum or breast milk within three days after birth. This evidence of the effect of telehealth interventions on breastfeeding rates is important as some of the short-term and long-term benefits of exclusive breastfeeding for children include healthier eating habits, reduced length of hospital stay, favourable weight increase, lower body mass index, lower adiposity, lower total cholesterol values, better cognitive and behavioural development, as well as stability of metabolic levels in children with metabolic disorders (Couto et al, 2020). Unfortunately, the existing evidence from this review (Lee et al, 2016) is of moderate quality and lacks the methodological rigor expected.…”
Section: Pre-pandemic Evidencementioning
confidence: 99%
“…Breast milk is the natural and optimal source of nutrition for the newborn; it is associated with multiple health bene ts (1,2), providing nutrients, hormonal immunoactives, and microbiomes necessary for growth and development (3). Furthermore, in the mother, it reduces the probability of breast and ovarian cancers, improves birth spacing, prevents type-2 diabetes, obesity and hypertension, among other bene ts (4,5).…”
Section: Introductionmentioning
confidence: 99%